Aktivitas Fisik dan Fungsi Kognitif Siswa - Tarigan, Beltasar; Hidayat, Teten; Angga Lardika, Rola (Universitas Nusantara PGRI Kediri, 2022)
Physical activity positively impacts cognitive function and can help avoid cognitive impairment. The study aimed to investigate the association between cognitive function and physical activity in junior high school students in Bandung. This research is quantitative research with a correlation analytic design. The instrument used in this study is a questionnaire. The sampling technique used is a random sample, the sample is 1870 respondents. The questionnaire used in this study is a closed questionnaire, which is a questionnaire whose answers have been provided so that respondents only need to choose. The study found that half of the respondents with less activity experienced less cognitive function (71,8%). Almost half of the respondents had a physical activity with good cognitive function (21.6%), and a small proportion of physical activity experienced quite a number of cognitive functions (8.6%). There is a relationship between physical activity and function cognitive in students. The results of this study are expected to be taken into consideration for further research by examining other factors related to cognitive function and other factors related to physical activity, such as gender, socioeconomic, and family factors.